Multi-State Models for Disease Natural History (Current Trends in Bayesian Methodology with Applications, 2015)
A variety of disease processes can be described through transitions between discrete states, such as stable or accelerated disease state in leukemia; development of AIDS-deﬁning illnesses in HIV; or diminished lung function in asthma patients. In progressive diseases, subjects traverse disease states inin Bayesianwhile in non-progressive diseases it is possible for subjects to experience repeated occurrences of some or all states.